Tranilast Inhibits Pulmonary Fibrosis by Suppressing TGFβ/SMAD2 Pathway - Kato M; Takahashi F; Sato T; Mitsuishi Y; Tajima K; Ihara H; Nurwidya F; Baskoro H; Murakami A; Kobayashi I; Hidayat M; Shimada N; et al. (Dove Medical Press, 2020)
Motoyasu Kato,1,2 Fumiyuki Takahashi,1,2 Tadashi Sato,1,2 Yoichiro Mitsuishi,1,2 Ken Tajima,1,2 Hiroaki Ihara,1,2 Fariz Nurwidya,1,2 Hario Baskoro,1,2 Akiko Murakami,1,2 Isao Kobayashi,1,2 Moulid Hidayat,1,2 Naoko Shimada,1– 3 Shinichi Sasaki,1,2 Reiko Mineki,4 Tsutomu Fujimura,5 Toshio Kumasaka,6 Shin-ichiro Niwa,7 Kazuhisa Takahashi1– 3 1Department of Respiratory Medicine, Juntendo University Graduate School of Medicine, Tokyo, Japan; 2Research Institute for Diseases of Old Ages, Juntendo University Graduate School of Medicine, Tokyo, Japan; 3Leading Center for the Development and Research of Cancer Medicine, Juntendo University Graduate School of Medicine, Tokyo, Japan; 4Laboratory of Proteomics and Biomolecular Science, Research Support Center, Juntendo University Graduate School of Medicine, Tokyo, Japan; 5Laboratory of Bioanalytical Chemistry, Tohoku Medical and Pharmaceutical University, Sendai, Miyagi, Japan; 6Department of Pathology, Japanese Red Cross Medical Center, Tokyo, Japan; 7Link Genomics, Incorporated, Tokyo, JapanCorrespondence: Motoyasu KatoDepartment of Respiratory Medicine, Juntendo University, Graduate School of Medicine, Bunkyo-Ku, Tokyo 113-8431, JapanTel +81-3-5802-1063Fax +81-3-5802-1617Email mtkatou@juntendo.ac.jpPurpose: Idiopathic pulmonary fibrosis (IPF) is characterized by the accumulation of extracellular matrix (ECM) protein in the lungs. Transforming growth factor (TGF) β-induced ECM protein synthesis contributes to the development of IPF. Tranilast, an anti-allergy drug, suppresses TGFβ expression and inhibits interstitial renal fibrosis in animal models. However, the beneficial effects of tranilast or its mechanism as a therapy for pulmonary fibrosis have not been clarified.Methods: We investigated the in vitro effect of tranilast on ECM production and TGFβ/SMAD2 pathway in TGFβ 2-stimulated A549 human alveolar epithelial cells, using quantitative polymerase chain reaction, Western blotting, and immunofluorescence. In vitro observations were validated in the lungs of a murine pulmonary fibrosis model, which we developed by intravenous injection of bleomycin.Results: Treatment with tranilast suppressed the expression of ECM proteins, such as fibronectin and type IV collagen, and attenuated SMAD2 phosphorylation in TGFβ 2-stimulated A549 cells. In addition, based on a wound healing assay in these cells, tranilast significantly inhibited cell motility, with foci formation that comprised of ECM proteins. Histological analyses revealed that the administration of tranilast significantly attenuated lung fibrosis in mice. Furthermore, tranilast treatment significantly reduced levels of TGFβ, collagen, fibronectin, and phosphorylated SMAD2 in pulmonary fibrotic tissues in mice.Conclusion: These findings suggest that tranilast inhibits pulmonary fibrosis by suppressing TGFβ/SMAD2-mediated ECM protein production, presenting tranilast as a promising and novel anti-fibrotic agent for the treatment of IPF.Keywords: tranilast, idiopathic pulmonary fibrosis, TGFβ, SMAD2